Feeding effectivity of the arfak rainbowfish, Melanotaenia arfakensis, Allen 1990 on difference of water turbidity level: a laboratory approach - Emmanuel Manangkalangi; M. F. Rahardjo; Renny K. Hadiaty; Sigid Hariyadi (Jurnal Iktiologi Indonesia, 2017)
The research on feeding effectivity of arfak rainbowfish conducted at Fisheries Laboratory, Faculty of Fishes and Marine Scince, University of Papua in July to December 2016. The purpose of this research is to describe feeding effectivity of the fish at several levels of water turbidity. The fish samples used in the treatment, collected from Nimbai Stream, Prafi River system, Manokwari were acclimatized for a month in the laboratory. The fish were selected based on the body length and categorized into six size classes. Each individual of the fish was treated with 200 individuals of mosquito larvae (instar IV stage) at seven turbidity levels (2.54, 25.07, 50.52, 100.20, 500.60, and 800.40 Nephelome-tric Turbidity Unit, NTU) using particles with size of <63um. Feeding effectivity was indicated by the level of preda-tion in a period of 15 minutes. The results of the research showed that average level of predation did not differ among size classes at the low level of turbidity (<50,52 NTU). The significant decrease in the average level of predation occurred at the higher level of turbidity (<100,12 NTU) with the values range from 23.2% to 65.9%. This indicated a decrease in the feeding effectivity as the turbidity levels increase. Abstrak Penelitian efektivitas ikan pelangi arfak dalam mencari makan dilaksanakan di Laboratorium Perikanan FPIK Univer-sitas Papua pada bulan Juli sampai Desember 2016. Tujuan penelitian ini untuk mendeskripsikan efektivitas ikan pela-ngi arfak mencari makan pada beberapa tingkat kekeruhan air. Contoh ikan yang digunakan dalam perlakuan dikoleksi dari Sungai Nimbai, sistem Sungai Prafi, Manokwari yang diaklimatisasi selama satu bulan di laboratorium. Individu ikan yang digunakan dalam penelitian ini dipilih berdasarkan panjang tubuh dan dikelompokkan ke dalam enam kelas ukuran. Setiap individu ikan diberi perlakuan pakan berupa larva nyamuk (tahap instar IV) sebanyak 200 individu pada tujuh tingkat kekeruhan yang berbeda (2,54; 25,07; 50,52; 100,20; 200,20; 500,60 dan 800,40 Nephelometric Turbidity Unit, NTU) dengan menggunakan partikel berukuran <63um. Efektivitas mencari makan akan ditunjukkan berdasarkan tingkat pemangsaan dalam periode 15 menit. Tingkat pemangsaan rata-rata tidak berbeda pada tingkat kekeruhan yang rendah (<50,52 NTU) dalam setiap kelas ukuran. Penurunan tingkat pemangsaan rata-rata secara nyata mulai berlang-sung pada tingkat kekeruhan yang lebih tinggi (<100,12 NTU) dengan nilai sebesar 23,2%-65,9%. Kondisi ini menun-jukkan penurunan efektivitas mencari makan seiring dengan semakin meningkatnya tingkat kekeruhan air.